Distance education : definition and glossary of terms - Schlosser, Lee Ayers; Simonson, Michael R. (Emerald Publishing Limited : Information Age Publishing, 2006)
Distance Education has become a major topic of interest in the field of educational communications and technology. In response to this interest, the Association for Educational Communications and Technology (AECT) published the first edition of Distance Education: Definition and Glossary of Terms in 2002. The second edition of this monograph was begun in 2005. While the definition of distance education was changed only slightly, the glossary of terms was updated significantly under the supervision of Joann Flick and members of AECT's Division of Distance Learning. The definition of distance education and much of the supporting narrative offered in this edition of Distance Education: Definition and Glossary of Terms is based on Teaching and Learning at a Distance: Foundations of Distance Education, 3rd. edition (2006). This information is used with permission.